TINDAK PIDANA PENGGUNAAN ALAT RAPID TES BEKAS PADA MASA PANDEMI COVID 19 - Tarigan, Tio Pilus (Gapenas Publisher, 2025)
When this rapid test becomes a travel requirement for prospective passengers, there is a case of using used rapid test kits at Kualanamu International Airport (KNIA). For this reason, it is necessary to study how criminal liability for the crime of using used rapid test kits during the Covid 19 pandemic and what is the role of the police in eradicating the crime of using used rapid test kits during the Covid 19 pandemic. The type of research used in writing this thesis is normative juridical which is descriptive analysis. The data collection technique used is library research. Criminal liability for the criminal act of using used rapid test kits during the Covid 19 pandemic is contained in a) Article 98 of Law Number 36 of 2009 concerning Health, paragraph (1) and paragraph 3 paragraph (3); b) Article 7 letters a and d of Law No. 8 of 1999 concerning consumer protection; c) Article 196 of Law Number 36 of 2009 concerning Health. The stipulation to hold corporations accountable in the form of accountability of their managers can also be seen in the provisions of Article 46 paragraph (2) of Law Number 7 of 1992: